Smallholder Agricultural Carbon Projects in Eastern Africa - Masiga, Moses; Nantongo Kalunda, Pauline; Kiguli, Lillian; Ssempala, Annet; Shames, Seth; Heiner, Krista; Miller, M (EcoAgriculture Partners, 2014)
This manual has been developed to help build the capacities of farmers, farmers groups, extension staff and project managers who are implementing agricultural carbon projects in Eastern Africa. The manual describes the steps for implementing an afforestation/reforestation voluntary carbon project based on the Plan Vivo Standard. It builds on experience gained by the Environmental Conservation Trust of Uganda (ECOTRUST), ENR Africa Associates, and EcoAgriculture Partners while undertaking a participatory action research project focusing on the institutional arrangements of smallholder agricultural carbon projects in Sub-Saharan Africa. This work was supported by the CGIAR Research Program on Climate Change, Agriculture, and Food Security (CCAFS).